Legal Protection of Users Wallet Electronic or E-Wallet - Benhard Kurniawan P; Irman Syahriar; Sarikun (PT Inovasi Pratama Internasional, 2023)
System payment through this online medium using electronic money as the payment tool. Drafts from electronic money This is payment in a modern way, that is, without There is physique the money or called with term cashless money. Then appear wallet electronic, or the current one known with the term e-wallet, that can be installed on a smartphone. Based on Bank Indonesia Regulation Article 1 Number 7 concerning Maintenance Processing Transaction Payment Number 18/40/PBI/2016, a container medium-based functional electronics can be equalized with place-saving electronic money as one of the methods of payment. Cannot be denied with existing payment through This e-wallet is very convenient in transactions, but it can also give rise to a new problem that can harm consumers as user e-wallet consequences lack of attention from perpetrator business e-wallet only important for getting profit. The writing method used in compiling papers This is method observation, that is, collecting data via purposeful observation to multiply references. Then method References, that is, use sources library, like books, articles, and so on. Constitution Protection: Consumers expected a capable law to give certainty to e-wallets. As a form of responsibility answer for losses that have been experienced by consumers, the perpetrator of business e-wallets has an obligation to give change, make a loss, and provide equal compensation for losses received by consumers. There is an accountability answer. This as form effort for grow return impact positive consumer to use e-wallet in do transaction electronic.